RESEARCH ON THE CHALLENGES AND SOLUTIONS FOR ACHIEVING GENDER EQUALITY IN PROFESSIONAL SPORTS - Nora DEDA (International Journal of Social and Educational Innovation)
This article examines the challenges faced by female athletes at the professional level, highlighting the obstacles encountered in their efforts to achieve success in professional sports. Gender inequality, insufficient funding, lack of institutional support, and societal stereotypes are some of the factors that continue to negatively impact the development of women’s sports. The article provides an analysis of the current state of women’s sports, including statistics and concrete cases that illustrate the differences in financial investments and support between women’s and men’s sports. The study is conducted through surveys directed at female athletes to gather data that helps identify the various obstacles they face. Furthermore, it discusses the importance of positive representation of female athletes in the media and the need to create a fairer and more equal environment in sports. In conclusion, the article presents policy and strategy proposals that can be implemented to alleviate these obstacles, emphasizing the importance of equal investment and support for female athletes as a crucial step toward achieving equality in sports.